Horizontal PGA Estimates for Varying Deep Geological Conditions—A Case Study of Banja Luka - Borko Bulajić; Silva Lozančić; Senka Bajić; Anka Starčev-Ćurčin; Miloš Šešlija; Miljan Kovačević; Marijana Hadzima-Nyarko (Applied Sciences)
In this study, the city of Banja Luka is used as a case study to evaluate horizontal PGA values in regions with a history of moderate to strong earthquakes and with different deep geological conditions. We present regional attenuation equations for PGA that can capture both the impacts of deep geology and local soil conditions. A PSHA study for a site in Banja Luka was carried out using the developed empirical scaling equations and compared to all previous seismic hazard estimations for the same region. The data indicate that variations in deep geological conditions may have a greater impact on PGA values than local soil effects. Given the scarcity of scaling equations that consider deep geology in addition to local soil conditions, we believe this case study is a step toward developing more accurate PGA estimates for comparable regions.